Identification of Asphalt Distribution and Thickness Using Drill Data - Nurfadli, Nurfadli; Widodo, Sri; Jafar, Nurliah (Journal of Geology and Exploration, 2024)
Cross section and block model of sediment is a method to determine the distribution and thickness of the deposition material is layered and constantly. The aim of this study to determine the direction of distribution of asphalt on the research area. Some of the activities carried out in advance starting from the analysis of core drilling, where this activity is to delineate the results of drilling activity to find out some impurities on the asphalt. Furthermore, the data obtained from the drilling include a collar of data, assay data, survey data and lithologic data is processed in tools that are customized. From the data processing result: string average A-A '17.571meters, string B-B' 14.142meters, string C-C '14.857meters, string D-D', 15meters string, E-E '11.142meters, string F-F' 12.75meters, and string G-G '15.833meters. From the results that have been obtained, it can be concluded that the average 14.47109 meters thick string and direction of spread slightly thickened to the west.